2019
DOI: 10.20537/vm190308
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of conditions for the appearance of high-speed bufting

Abstract: Численно исследуется явление возникновения скоростного бафтинга при обтекании профиля NACA0012 трансзвуковым потоком. Формулируется математическая модель, основанная на алгоритмах высокого порядка аппроксимации, позволяющая рассчитывать нестационарные отрывные течения. Модель базируется на интегрировании квазигидродинамических уравнений. Проводится параметрическое исследование обтекания профиля высокоскоростным потоком вязкого газа в зависимости от угла атаки. Анализируются как мгновенные, так и осредненные ка… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…But taking into account that the experi-ment reproduces a three-dimensional flow, and the simulation is two-dimensional, the results can be considered quite satisfactory. The authors of [22] showed that a lambda-shaped shock wave is formed on the backwind side. Behind the leg of the lambda-shaped shock, the flow is separated from the profile surface.…”
Section: D Simulation Of the Buffet Onsetmentioning
confidence: 99%
See 1 more Smart Citation
“…But taking into account that the experi-ment reproduces a three-dimensional flow, and the simulation is two-dimensional, the results can be considered quite satisfactory. The authors of [22] showed that a lambda-shaped shock wave is formed on the backwind side. Behind the leg of the lambda-shaped shock, the flow is separated from the profile surface.…”
Section: D Simulation Of the Buffet Onsetmentioning
confidence: 99%
“…Also in [22], the changes in the coefficients over time are analyzed. At an angle of attack of 5 degrees, the fluctuations in the coefficients are insignificant.…”
Section: D Simulation Of the Buffet Onsetmentioning
confidence: 99%